Landfill Leachate Management - Tyagi, Vinay Kumar; Ojha, C.S.P (IWA Publishing, 2024)
Landfill leachate is a complex mix of organics, inorganics and heavy metals produced from the conventional and engineering landfilling practices. The adverse effects of landfill leachate on the human and environmental health have forced the relevant authorities to stipulate stringent disposal requirements, producing the requirement for ground-breaking technological solutions for effective management of landfill leachate. The researchers and field engineers are still looking for robust options for leachate management. This timely book on landfill leachate management is a valued addition into this domain. The key features of the book include: broad range of treatment techniques covered, conventional to advanced technological options discussed, along with the inclusion of successful case studies.